Transport hysteresis of core plasma, isotope effect, and H-mode physics. (30th September 2016) - Itoh, S.-I.; Itoh, K.; Inagaki, S.
Abstract: This article assesses the understanding of and impact by the hysteresis in transport relation. The rapid changes of fluxes compared to slow changes of plasma parameters are overviewed for both edge barrier and core plasmas. The theoretical approaches to understanding the direct influence of heating power on turbulent transport are addressed. Based on this new theoretical framework, the 'isotope effect' of plasma confinement time is discussed. A trial explanation is given for this unresolved mystery in plasma confinement. The advanced data analysis method to research the hysteresis in gradient-flux relation is explained.